2021
DOI: 10.3934/publichealth.2021048
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of SIR Model, Linear Regression, Logistic Function and ARIMA Model for forecasting COVID-19 cases

Abstract: <abstract> <p>Starting February 2020, COVID-19 was confirmed in 11,946 people worldwide, with a mortality rate of almost 2%. A significant number of epidemic diseases consisting of human Coronavirus display patterns. In this study, with the benefit of data analytic, we develop regression models and a Susceptible-Infected-Recovered (SIR) model for the contagion to compare the performance of models to predict the number of cases. First, we implement a good understanding of data and perform Explorator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Among the latter, ARIMA (autoregressive integrated moving average) and SARIMA (ARIMA + seasonal component) models have shown excellent predictive capabilities. In particular, a recent study by Abolmaali and Shirzaei demonstrated that the ARIMA approach could outperform other classical models such as logistic function, linear regression, and SIR [11]. Similar findings were obtained by Alabdulrazzaq et al, who proved that the accuracy of the prediction of COVID-19 spread provided by their ARIMA model was both appropriate and satisfactory [12].…”
Section: Introductionsupporting
confidence: 69%
“…Among the latter, ARIMA (autoregressive integrated moving average) and SARIMA (ARIMA + seasonal component) models have shown excellent predictive capabilities. In particular, a recent study by Abolmaali and Shirzaei demonstrated that the ARIMA approach could outperform other classical models such as logistic function, linear regression, and SIR [11]. Similar findings were obtained by Alabdulrazzaq et al, who proved that the accuracy of the prediction of COVID-19 spread provided by their ARIMA model was both appropriate and satisfactory [12].…”
Section: Introductionsupporting
confidence: 69%
“…Abolmaali & Shirzaei [11] have compared the results of different models (SIR Model, linear regression, logistic function, ARIMA) in the prediction of confirmed COVID-19 cases in 2021. Although the linear regression model performs well in short-term prediction, overall, the ARIMA model is still better than other models.…”
Section: Autoregressive Integrated Moving Average (Arima)mentioning
confidence: 99%
“…The findings demonstrate that Pearson VII universal kernel-based Support Vector Machine outperform other methods by achieving 98.81% accuracy and MAE of 0.012. To predict the number of cases in four nations, Abolmaali and Shirzaei ( 2021 ) employed logistic function, linear regression, Susceptible-Infected-Recovered (SIR) model, and ARIMA model. The models are evaluated using MSE.…”
Section: Related Workmentioning
confidence: 99%